Pengurusan Fatwa Di Negara-Negara Nusantara - Pengurusan Fatwa Di Singapura - Khairul Anuar Mohamad; Azman Ab. Rahman; Adel M. Abdulaziz (Universiti Sains Islam Malaysia, 2024)
The research entitled "Fatwa Management in Asean: Fatwa Management in Singapore" was conducted due to the important role that fatwa management plays in publishing and explaining problems and matters related to muslim society. The effectiveness of fatwa in explaining an issue is not only based on its strong evidences but also depended on the implementation of modern technology in fatwa management. Singapore, a country where muslims are minority has its own council that is responsible for all muslim activities and matters including the management of fatwa, called Majlis Ugama Islam Singapura (MUIS). All matters related to muslim that demand fatwa to be issued such as newwater issue will be analyzed by a fatwa committee consist of a mufti, two experts in Islam from the highest committee in MUIS and two ustaz who are recognized by the society. They conduct a meeting to discuss the problem issued and analyze it referring to principles of Islamic jurisprudence and conduct the second meeting to reach the final decision. The fatwa fither on, will be announced and published in the form of internet, risalah and fatwa book. It is concluded that fatwa management in Singapore is well organized and has an effort in solving the confision regarding Islamic matters or problems faced by the muslim there.